Why and how is the self related to the brain midline regions? - Niall W Duncan (Frontiers Research Topics, 2014)
What the self is and where it comes from has been one of the great problems of philosophy for thousands of years. As science and medicine have progressed this question has moved to also become a central one in psychology, psychiatry, and neuroscience. The advent of in vivo brain imaging has now allowed the scientific investigation of the self to progress further than ever. Many such imaging studies have indicated that brain structures along the cortical midline are particularly closely related to self-specific processing. This association between cortical midline structures (CMS) and self is reinforced by the involvement of these regions in other self-oriented processes, such as mind-wandering or stimulus valuation. Those midline regions involved in self- processing also overlap with another network, the default mode network, which shows high brain activity during the so-called resting state, indicating that there may be a special relationship between self-processing and intrinsic activity. Although such promising groundwork linking the self and CMS has been carried out, many questions remain. These include: what features of the midline regions lead to their apparent importance in self-processing? How can we appropriately account for confounding factors such as familiarity or task-effects in our experiments? How is the self-related to other features of the mind, such as consciousness? How is our methodology influencing our attempts to link the self and the brain? The purpose of this ebook is to address some of these questions, including opinions, perspectives, and hypotheses about the concept of the self, the relationship between CMS and the self, and the specific function of these brain regions in self-processing. It also includes original research papers describing EEG, fMRI, and behavioral experiments investigating different aspects of the self.